Socio-economic constraints in re-entering the labour market during COVID-19 crisis and the resilience of female workers living in urban informal settlements - Nur, Jahid (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Development Studies, 2021.